Road Improvement and Deforestation in the Congo Basin Countries - Damania, Richard (World Bank, Washington, DC, 2015)
Road construction has often been viewed as the precursor to deforestation, especially in tropical forests. Traditional responses to such threats have been reactive, with attempts to mitigate impacts through physical measures, or the establishment of protected areas. These approaches often have not been entirely successful, especially in areas where economic potential is significant. This paper seeks to mitigate such conflicts by proposing a proactive approach to development planning and environmental policy. It develops a high-resolution spatial model of road improvement impacts that includes ecological risks and the economics of forest clearing. The approach is implemented by estimating the potential impact of road upgrading on forest clearing and biodiversity in eight Congo Basin countries. The paper demonstrates how the detailed analysis can identify areas of high ecological priority as well as areas at high risk of forest loss. The paper contributes to several aspects of the literature. First, it provides the most recent and reliable estimates of the drivers of deforestation in the Congo Basin, with the latest high-resolution satellite data on forest cover changes. Second, it presents novel estimates of biodiversity threats by creating an index that combines and synthesizes several measures of biodiversity loss and impacts. It then develops an empirical framework for estimating the ecological impacts of road improvement. Finally, the paper illustrates how the empirical framework can be used to preempt impacts and avoid potential ecological damage.